The influences of shank mass and inertia manipulation on sprint kinetics - Yang, C.; Yu, J.; Sun, Y.; Zhuang, W.; Liu, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to investigate the kinetics changes caused by the lower extremities mass and inertia, explore the mechanics of this training method and provide theoretical instruction for sprinting training. 18 male sprinters were recruited and required to sprint with different lower extremities loading conditions (0%, 10%, 15% of the shank mass). The data was collected using high speed infrared motion capture system and force plates. 15% of the shank mass loading made the joints torque and power decrease significantly, while the torque of knee significantly increased at the toe-off moment. In addition, the ankle absorbed more energy during the stance phase as well as the knee generated more energy during the swing phase. The result showed that changes of the joints torque and power attribute to the location of the loadings.